Religion and Public Opinion Toward Same-Sex Relations, Marriage, and Adoption: Does the Type of Practice Matter? - Perry, Samuel L. (Journal for the scientific study of religion, 2016)
This study examines how religion's impact on Americans' attitudes toward same-sex practices varies by the type of practice being considered. We theorize that same-sex romantic and family practices such as sexual relations, marriage, and adoption represent distinct practice types, differing in degrees of legality, cultural legitimacy, and in their internal power dynamics. Consequently, we expect that Americans view each practice type somewhat differently and their opinions on each may be influenced by religion in distinctive ways. Drawing upon national-level data, we estimate and compare the relative net effects of a comprehensive battery of religious measures on support for gay sex, marriage, and adoption, both for the full sample and across religious traditions. Analyses demonstrate that public opinion toward gay sexual relations is more strongly related to religious practice and theological conservatism compared to attitudes regarding same-sex marriage or adoption. Moreover, frequent religious practice and conservative theological beliefs about the Bible tend to be more strongly associated with attitudes toward same-sex relationships for evangelicals, compared to mainline Protestants and, to a lesser extent, Catholics. Findings ultimately affirm that the type of same-sex practice being considered (sex, marriage, or adoption) serves to moderate religions' impact on Americans' support for such practices.